Taplau: Wajah Baru Kawasan Pantai Padang Menuju Wisata Halal di Kota Padang - Ade Irwandi; Riana Putri (Prodi Sosiologi FISIP Universitas Teuku Umar, 2022)
The development of halal tourism in Indonesia, was initiated by the Indonesian Ministry of Tourism and Creative Economy, which has formed a Halal Tourism Development Acceleration Team and carried out the development in 10 National Priority Halal Destinations that refer to the GMTI (Global Muslim Travel Index) standard. In West Sumatra, especially Padang City has a large Muslim population of around 90%. This is because the city of Padang is also an urban center, so there are still many Minangkabau people living and not many immigrants. So that the City of Padang is currently working on halal tourism, especially in Padang Beach. The purpose of this study is to describe and describe the development of the Padang Beach area as a halal tourist destination in the city of Padang. By using qualitative methods, data collection uses observation, interviews and literature studies so that data can be collected from informants in the form of traders, visitors (tourists) and tourism managers. This paper shows that the Padang Beach area has problems in the form of many flat umbrellas, dirty, unmanaged traders, buskers, blasphemy, lack of supporting facilities (places of worship, parking and toilets) and not pedestrian friendly. So that the span of 2014 until now has been carried out by the Padang City government. So that at this time a new face has made it one of the leading tourism in the city of Padang. development such as pedistrians, arrangement of traders (PKL), clean, availability of parking lots, toilets, mosques and many cafes and coffee shops located in LPC (Lapau Panjang Cimpago). However, these efforts do not fully make the Padang Beach area a halal tourism area. there are still many development and structuring efforts to be able to realize taplau as a halal tourist destination in the city of Padang. This is related to halal certification, where there are no halal-certified hotels and restaurants in the Padang Beach area.